Understanding Project Leadership: An Indian Context. Issue 2 (July 2019) - Bansal, Nidhi; Singh, Shipra; Srivastava, D. K.
Abstract: The role of project leaders is critical in the success of any project. Understanding the project leadership dimensions in the unique Indian context would be beneficial for both scholars and practitioners. The current study attempts to explore the project leadership dimensions from the Generation Y's (Gen Y) project team members' perspective. The study adopted a qualitative methodology by conducting semi-structured interviews. These interviews were taken during January 2017–March 2017. A total of 25 project's team members were interviewed for the study. Mainly, five themes have emerged after analyzing interview transcripts, namely meaning of leadership, leadership qualities, and the role of culture in leadership, the difference between leaders and managers, and examples of good and bad leaders. The findings of the study will give direction to the project leaders, this, in turn, may lead to the success of the project. Future research may empirically examine the factors identified from the study on Gen Y sample population in the Indian context.